THE ARTISTIC POTENTIAL OF IMMERSIVE TECHNOLOGIES IN UKRAINIAN DESIGN - Mulkokhainen, Viktoriia; Boiko, Valeriia (Theory and practice of design, 2024)
Purpose. The research purpose is to determine the role of immersive technologies (augmented, virtual, mixed and extended reality technologies) in creating an artistic image of relevant contemporary Ukrainian design projects. Methodology. The study is based on a methodological system that includes generalization, comparison, induction, deduction, analogy, as well as theoretical and analytical methods. Results. The artistic representation of design projects endowed with immersive features is carried out simultaneously at several levels by layering various features of artistic expression. At the same time, the traditional compositional, coloristic, stylistic, textural, and other tools of artistic expression are supplemented by innovative ones, provoked by a complex synthesis of different components within one project: dynamic, interactive, and multimedia. Moreover, semantic features, which come to the fore in that interpretation (e.g., the works of digital fashion model designers), are often involved in the development of the artistic image of an immersive-modified project. Thus, the artistic image acquires, in addition to visual characteristics, sound, semantic and dynamic ones, which no less actively affect the audience’s perception by enhancing or suppressing the visual effect. As a result, the same visual effect, with or without the support of immersive technologies, can convey a completely different project idea. Scientific novelty. The present article demonstrates an innovative approach to assessing rapid innovations in Ukrainian design, which is a response to global technological trends. In particular, the authors put forward a model for constructing the artistic and design image of the relevant works in the context of the active implementation of immersive technologies. It is a multi-layered structure of the internal interaction of specific visual factors and their impact on the viewer. Practical relevance involves the timely analysis of current trends, which can both guide practitioners in the dynamic field of contemporary design activity and specify the vectors of subsequent transformations that have potential to succeed.